Reproductive biology of paradise threadfin Polynemus paradiseus (Linnaeus, 1758) from Shibsa River in Bangladesh - Naser Abu; Ahmmed Shawon; Parvin Shahanaj; Islam Latiful; Rashid Harunur; Mahmud Yahia (BIO Web of Conferences, 2023)
The paradise threadfin, Polynemus paradiseus is one of the commercially important brackishwater finfish of the family Perciformes in Bangladesh. The present study aimed to investigate the reproductive biology of paradise threadfin from Shibsa River in Bangladesh. The fish samples (66) were collected from May 2021 to April 2022. The relationship between body weight (BW) and total length (TL) of sampled fish were analyzed with a non-linear power equation where R2 = 0.915 and ‘b’ value (3.22) indicates a positive allometric growth pattern. Linear relationship indicates gonad weight (GW) increases with the BW and fecundity increases with BW, TL, GW and gonadosomatic index (GSI). The highest GSI was recorded in June (11.10±0.91), whereas, the lowest in November (0.44±0.08). The maximum fecundity was found in June (32410±7790). Ovarian histology displayed different stages of oocyte development. Late yolk granule stage (LYGS) was found in the months of September-October and May-July, respectively. Based on the GSI, fecundity and ovarian histology, it was revealed that the spawning season of P. paradiseus was from May to October with a major peak in June and minor one in September. The knowledge on different aspects of reproductive biology of paradise threadfin would be helpful for planning captive breeding and to design sustainable management policies for conservation of this species in the south-west coast of Bangladesh.